Development of rapid and selective epoxidation of α-pinene using single-step addition of H2O2 in an organic solvent-free process. Issue 52 (7th October 2021) - Mukhtar Gunam Resul, Mohamad Faiz; Rehman, Abdul; López Fernández, Ana María; Eze, Valentine C.; Harvey, Adam P.
Abstract : Products obtained from the oxidation of α-pinene with hydrogen peroxide (H2 O2 ) in the presence of tungsten-based polyoxometalates (α-pinene 1, α-pinene oxide 2, pinanediol 3, campholenic aldehyde 4, sobrerol 5, verbenol 6 and verbenone 7 ). Abstract : This study reports substantial improvement in the process for oxidising α-pinene, using environmentally friendly H2 O2 at high atom economy (∼93%) and selectivity to α-pinene oxide (100%). The epoxidation of α-pinene with H2 O2 was catalysed by tungsten-based polyoxometalates without any solvent. The variables in the screening parameters were temperatures (30–70 °C), oxidant amount (100–200 mol%), acid concentrations (0.02–0.09 M) and solvent types ( i.e., 1, 2-dichloroethane, toluene, p -cymene and acetonitrile). Screening the process parameters revealed that almost 100% selective epoxidation of α-pinene to α-pinene oxide was possible with negligible side product formation within a short reaction time (∼20 min), using process conditions of a 50 °C temperature in the absence of solvent and α-pinene/H2 O2 /catalyst molar ratio of 5 : 1 : 0.01. A kinetic investigation showed that the reaction was first-order for α-pinene and catalyst concentration, and a fractional order (∼0.5) for H2 O2 concentration. The activation energy ( E a ) for the epoxidation of α-pinene was ∼35 kJ mol −1 . The advantages of the epoxidation reported here are that the reaction could be performed isothermally in an organic solvent-free environment to enhance the reaction rate, achieving nearly 100% selectivity to α-pinene oxide.